THE CORRELATION OF FREE ACCESS TO THE SEA AND SOVEREIGNTY OF THE STATES IN THE INTERNATIONAL LAW OF THE SEA - Abovyan, Arthur (State and Law, 2023)
The problem of ensuring the rights of the Landlocked States in the Law of the Sea is expressed in the emphasized confrontation between the principles of Sovereignty and Freedom of the High Seas. The content of the principles of Sovereignty and Freedom of the High Seas in the Law of the Sea is analyzed in the article, and it also presents the necessary prerequisites for realizing of the right of Landlocked States to Free Access to the Sea. The conventions concerning the rights of Landlocked States are subject to a comparative analysis in the article, it as well discusses the changes in the content of the right of Access to the Sea. The article addresses the nuances of the right of transit in the Law of the Sea and in International Economic Law. As a result of the study, conclusions are drawn in regard to the reduction of the dominant influence of the Sovereignty principle in the Law of the Sea.